An Analysis of Post-Product Development Market Research and its Effects on Firms and Consumers - Randal Reed (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1992)
This paper examines a model of post-product development market research that allows firms to improve their information about demand curves. The process does not allow perfect information at finite expenditure levels. The model examines oligopolistic behavior and social welfare in the heterogeneous product world. The basic results derived are that investment of this type bears no externality to other firms in the market and a negative externality to consumers in the market from the improved information of the firm. These results are robust across several extensions which are presented in the paper. Conclusions for policy toward firms engaging in post-product market research are drawn for several different international market scenarios.
Keywords: 330